Edukasi tentang Kesehatan Jiwa pada Remaja di SMP IT Nurul Ilmi Kota Jambi - Hesty, Hesty; Maimaznah, Maimaznah; Indrawati, Iin (3031-8572, 2023)
Mental health problems occur in 15 -22% of children and adolescents, but less than 20% receive treatment. The diagnosis of mental disorders in children and adolescents is behavior that is inappropriate for their age level, deviant compared to cultural norms which results in a lack or disruption of adaptive functioning. Poor adolescent mental health occurs due to a lack of knowledge or awareness about mental health. According to the Counseling Guidance teacher, the problems that are often encountered by students are emotional instability, attitude in speaking as they like, grade 9 students are confused about where to continue after graduating. One way to increase knowledge is to provide education to students about mental health in adolescents, including definitions, causes, signs and symptoms, management and prevention. Changes in students' attitudes from negative attitudes to positive attitudes about emotions, anxiety and depression. This community service activity was carried out for 20 students from Nurul 'Ilmi IT Middle School, Jambi City. Education can be carried out using various types of media, one of which is in the form of modules/leaflets. The provision of education is agreed upon in groups to facilitate the delivery of information and takes place in the hall. Community service methods include lectures, discussions and sharing experiences. The results were an increase in knowledge about mental health and changes in attitudes among students.